2010
DOI: 10.1161/hypertensionaha.110.154518
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 1B1 Contributes to Angiotensin II–Induced Hypertension and Associated Pathophysiology

Abstract: Abstract-Hypertension is the leading cause of cardiovascular diseases, and angiotensin II is one of the major components of the mechanisms that contribute to the development of hypertension. However, the precise mechanisms for the development of hypertension are unknown. Our recent study showing that angiotensin II-induced vascular smooth muscle cell growth depends on cytochrome P450 1B1 led us to investigate its contribution to hypertension caused by this peptide. Angiotensin II was infused via miniosmotic pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
83
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 44 publications
4
83
0
Order By: Relevance
“…Our finding that the CYP1B1 inhibitor 2,3′,4,5′‐tetramethoxystilbene minimizes hypertension, atherosclerosis, and abdominal aneurysms,5, 28, 29 while also attenuating neointimal growth in wire‐injured carotid artery of Cyp1b1 +/+ male mice, further supports our hypothesis that CYP1B1 is required for neointimal growth and suggests an important translational implication of this work. Thus, CYP1B1 could serve as a potential target for the development of novel agents for the treatment of restenosis after balloon angioplasty, or to coat drug‐eluting stents as antiproliferative agents in male mice.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our finding that the CYP1B1 inhibitor 2,3′,4,5′‐tetramethoxystilbene minimizes hypertension, atherosclerosis, and abdominal aneurysms,5, 28, 29 while also attenuating neointimal growth in wire‐injured carotid artery of Cyp1b1 +/+ male mice, further supports our hypothesis that CYP1B1 is required for neointimal growth and suggests an important translational implication of this work. Thus, CYP1B1 could serve as a potential target for the development of novel agents for the treatment of restenosis after balloon angioplasty, or to coat drug‐eluting stents as antiproliferative agents in male mice.…”
Section: Discussionsupporting
confidence: 81%
“…We have previously reported that ROS generated via CYP1B1 contribute to the development of hypertension in different animal models, atherosclerosis, and abdominal aortic aneurysms 5, 28, 29. In the current study, wire injury of the carotid arteries increased superoxide production, as detected by 2‐hydroxyethidium fluorescence in Cyp1b1 +/+ mice, which was reduced in Cyp1b1 −/− mice.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…12 Briefly, tissue samples were homogenized (2 Â 3 minutes) in ice-cold 100 mmol/L potassium phosphate buffer (pH 7.4) using the TissueLyser II (Qiagen, Valencia, CA). Centrifugation was performed at 10,000 Â g for 20 minutes at 4 C. Protein contents in the samples were determined by the Bradford method, 500 mg of protein was added to a reaction mixture containing 20 mmol/L L-CEE substrate and 100 mmol/L potassium phosphate buffer (pH 7.4) and incubated at 37 C for 10 minutes, 100 mmol/L of NADPH (final concentration) was added, and the solution was further incubated at 37 C for 45 minutes.…”
Section: Role Of Cyp1b1 In Aortic Aneurysmsmentioning
confidence: 99%
“…7,8 The metabolism of fatty acids by cyclooxygenase (COX), lipoxygenase, and cytochrome P450 (CYP) enzymes results in the generation of ROS, 8,9 and ROS generated via the activation of NADPH oxidase appears to play a major role in the development of AAA. 10 Previously, we have shown that Ang IIeinduced vascular smooth muscle cell (VSMC) migration, proliferation and hypertrophy, 11 and hypertension 12 depend on CYP1B1, 11,12 a heme-thiolate monooxygenase that is expressed in extrahepatic tissues, including those in the cardiovascular system, 13 and is involved in activating NADPH oxidase and generating ROS. 11e13 These observations led us to the hypothesis that Ang IIeinduced AAA and associated pathogenesis are mediated by CYP1B1-generated ROS.…”
mentioning
confidence: 99%